Ancestral Legitimization and Syncretic Islam in the Wayang Klithik of Gotanjung’s Sedekah Bumi - Selviawati, Evi; Syahrial, Syahrial (Institut Seni Indonesia Denpasar, 2026)
Wayang klithik is a two-dimensional wooden puppetry tradition found in Central and East Java. In Gotanjung Village, Pati Regency, Central Java, wayang klithik is performed every year as part of sedekah bumi ceremony, a ritual to express gratitude for agricultural blessings. This study analyzes how wayang klithik in Gotanjung’s sedekah bumi functions as a ritual performance in which ancestral legitimation within a syncretic Islamic framework serves as a mechanism that sustains the tradition. It also examines how sedekah bumi and wayang klithik work together in reinforcing Gotanjung’s agrarian identity. Employing a performative ethnographic method, data were collected through field observations, interviews with key informants, and focus group discussions. The findings reveal that wayang klithik performance in sedekah bumi plays a crucial role in demonstrating the practice of tawassul through ancestral figures within syncretic Islam, providing a case study of how local cosmology and religious syncretism intersect to sustain cultural legitimacy. The study contributes to understanding how Islamic devotional practices are negotiated within a Javanese cosmocentric framework through ritual performance, offering insights for the preservation of both sedekah bumi and wayang klithik traditions.